Environmental impacts and infrastructure in Agrarian Reform settlements in Minas Gerais, Brazil (Sustainability in Debate, 2020)
The existence of adequate infrastructure aims to meet the basic human needs, contributing to local development, poverty reduction and social inequalities. The aim of this article is to analyze the potential environmental impacts arising from infrastructure conditions in agrarian reform settlements in the State of Minas Gerais - Brazil. The methodology is based on the Leopold Matrix, which considers the environmental components: water pollution, soil degradation, land use and quality of life, in a sample of 1,270 lots. The variables analyzed were: water supply; sanitation; disposal of wastewater, dry waste, pesticide packaging and veterinary medicinal products; distribution of electricity and paving of public roads. The results indicate that the impacts are of greater negative potential in the Northern Mesoregion of Minas Gerais (70%), followed by Triângulo Mineiro/Alto Paranaíba (60%), proving the hypothesis that the incipience in infrastructure conditions results in a greater negative environmental impact.